A penetrating atherosclerotic ulcer rapidly growing into a saccular aortic aneurysm during treatment of leukaemia: a case report. Issue 7 (12th July 2021) - Takeuchi, Shinsuke; Takayama, Nobuyuki; Soejima, Kyoko; Yoshino, Hideaki
Abstract: Background: The clinical course of penetrating atherosclerotic ulcers is variable and can be complicated with intramural haematomas, dissection, pseudoaneurysms, or aortic rupture. Because it can lead to life-threatening conditions, it needs to be managed carefully. Case summary: A 68-year-old woman, who was treated for acute myeloid leukaemia (subtype: M0-FAB) approximately 1 year before presentation, visited the hospital with complaints of a headache and lumbar pain. After hospitalization, investigations revealed miliary tuberculosis. On the same day, she developed a Stanford type A acute aortic dissection (AAD) with cardiac tamponade; during the course of the previous leukaemia treatment, a small ulcerative lesion at the distal aortic arch grew into a small saccular aortic aneurysm (SAA) that expanded rapidly and finally developed into a Stanford type A AAD. However, the relationship between the SAA and aortic dissection could not be confirmed. Discussion: The chronological changes in the atherosclerotic lesion at the distal aortic arch could be clearly observed because computed tomography scans were repeatedly obtained until just before the onset of AAD. The rapid progression of atherosclerotic lesions in the unique context of leukaemia treatment and miliary tuberculosis was considered to be a pathological characteristic, and the mechanism underlying this process was investigated. Clinicians should be aware of the aortic complications that may progress under special circumstances, such as anthracycline use or immunodeficiency. Careful observation is mandatory for patients with aortic disease.